Child Support Grant Policy and Poverty Alleviation: Is there a link in Mamelodi Township, Gauteng Province - PROMISE RASEALA; NOZUKO HLWATIKA (African Journal of Governance and Development, 2022)
When governments around the world engage in public policy-making, quite often, the public officials and policy-makers are faced with discreet opposition from non-government organisations trade unions and civil societies. The public policymakers usually go ahead with the implementation of the suggested policy. For example, in South Africa (SA), Child Support Grant (CSG) was implemented in an attempt to alleviate poverty. This can be attributed to many factors, such as urgency in addressing the poverty gap in society and lack of interest from the members of the public in public policy-making. Based on capability and social security approach/strategy and rational approach, this study explores an outcomes-based evaluation of the CSG policy and its relationship with poverty alleviation in Mamelodi Township, Gauteng Province, SA. The empirical results indicate that there is a linkage or relationship between the reduction of poverty levels and the implementation of the CSG policy in Mamelodi Town.